Maternal asthma, breastfeeding, and respiratory outcomes in the first year of life. Issue 7 (6th April 2020) - Harvey, Soriah M.; Murphy, Vanessa E.; Gibson, Peter G.; Collison, Adam; Robinson, Paul; Sly, Peter D.; Mattes, Joerg; Jensen, Megan E.
Abstract: Maternal asthma increases the risk of infant wheeze. Breastfeeding may offer protection but there is limited evidence in this high‐risk group. We examined associations between breastfeeding and respiratory outcomes, in infants born to women with asthma. This study was a secondary analysis of two prospective cohorts of pregnant women with asthma, and their infants, conducted between 2007 and 2018. At 6 ± 1 (T1) and 12 ± 1 (T2) months post‐partum, mothers reported breastfeeding patterns and infant wheeze (primary outcome), bronchiolitis, and related medication use and healthcare utilization, via a validated questionnaire; a subgroup completed face‐to‐face interviews. χ 2 tests and logistic regression models, adjusting for confounders, were utilized. Data were complete for 605 participants at T1 and 486 (80%) at T2. Of 605 participants: 89% initiated breastfeeding and 38% breastfed for more than 6 months. Breastfeeding for more than 6 months vs "never" was associated with a reduced adjusted relative risk of infant wheeze at T1 (0.54, 95% confidence interval, 0.30‐0.96). Bronchiolitis risk was reduced at T1 and T2 with more tha 6 months of breastfeeding vs "never." Breastfeeding duration of 1 to 3 months, 4 to 6 months, and more than 6 months were associated with a reduced risk of infant healthcare utilization (all P  < .05, vs "never"), but not medication use ( P  > .05). Breastfeeding for more than 6 months was associated with a reduced risk of wheeze, bronchiolitis, and wheeze‐related healthcare utilization in infants at risk due to maternal asthma. Notably, breastfeeding for shorter durations was associated with a reduced risk of healthcare utilization compared with none. Larger cohorts are needed to further examine the impact of breastfeeding exposure on respiratory health in infants exposed to maternal asthma.